Sistem Informasi Kunjungan KB Menggunakan Teknologi SMS Guna Meningkatkan Kepatuhan Akseptor KB (Information System Visitation KB Using SMS Technology To Increase Compliance Acceptors) - Trismianto Asmo Sutrisno; Surati Ningsih (Indonesian Journal on Medical Science, 2015)
Abstract: This research aims to develop visited information systems for family planning acceptor using Short Message Service (SMS) technology in order to improve compliance acceptors especially acceptor injections to come for a visit in accordance with the schedule. This research approach using the System Development Life Cycle (SDLC) with Waterfall model. While the software development carried out in phases: 1) analysis of software requirements, 2) design, 3) coding and 4) testing. Step research by collecting data with survey method by field observations and interviews with speakers and literature. Observations and interviews were conducted in order to obtain accurate data on contraception, especially injectable contraceptives, re-establishment of the scheduled visit and other supporting information. Furthermore, process data that have been obtained to be processed using SDLC approach with Waterfall model and eventually managed to produce a model research information system using SMS technology to improve compliance acceptors are implemented in Independent Practice Midwife (BPM) Susiana Amini cottage located in the village of District Sukoharjo Central Java Province.Keywords: Information Systems, Family Planning, SMS, AcceptorsÂ Abstrak: Penelitian ini bertujuan untuk mengembangkan sistem informasi kunjungan akseptor Keluarga Berencana (KB) menggunakan teknologi Short Message Service (SMS) guna meningkatkan kepatuhan akseptor KB khususnya akseptor KB suntik untuk datang berkunjung sesuai dengan jadwal. Penelitian ini menerapkan pendekatan menggunakan metode System Development Life Cycle (SDLC) dengan model Waterfall. Sedangkan pengembangan perangkat lunak dilaksanakan dengan tahapan:Â  1) analisis kebutuhan perangkat lunak, 2) desain, 3) pembuatan kode program dan 4) pengujian. Langkah penelitian dengan melakukan pengumpulan data dengan metode survey dengan cara observasi lapangan dan wawancara kepada narasumber serta studi pustaka. Observasi dan wawancara dilakukan guna memperoleh data yang akurat tentang kontrasepsi KB khususnya kontrasepsi suntik, penetapan jadwal kunjungan ulang serta informasi pendukung lainnya. Selanjutnya mengolah data-data yang telah diperoleh untuk diolah menggunakan pendekatan SDLC dengan model Waterfall sehingga pada akhirnya penelitian berhasil menghasilkan model sistem informasi menggunakan teknologi SMS guna meningkatkan kepatuhan akseptor KB yang diimplementasikan di Bidan Praktek Mandiri (BPM) Susiana Amini yang terletak di desa Pondok Kabupaten Sukoharjo Provinsi Jawa Tengah.Kata kunci: Sistem Informasi, Keluarga Berencana, SMS, Akseptor